Dicationic liquid mediated synthesis of tetrazoloquinolinyl methoxy phenyl 4-thiazolidinones and their antibacterial and antitubercular evaluation - Deshmukh, A. R.; Dhumal, S. T.; Nawale, L. U.; Khedkar, V. M.; Sarkar, D.; Mane, R. A. (Synthetic Communications, 2019)
In a search of new potentially active antitubercular agents here we have synthesized 3-substituted phenyl-2-(4-(tetrazolo[1,5-a]quinolin-4-ylmethoxy)phenyl)thiazolidin-4-ones (8a–l) and evaluated their antibacterial, particularly antitubercular activity. These have been conveniently synthesized by performing one–pot cyclocondensation of 4-(tetrazolo[1,5-a]quinolin-4-ylmethoxy)benzaldehyde, anilines and mercaptoacetic acid in dicationic ionic liquid, (3-methyl-1-[3-(methyl-1H-imidazolium-1-yl)propyl]-1H-imidazolium dibromide [C3(MIM)2–2Br]) and obtained excellent yields of (8a–l). 4-Thiazolidinones (8a–l) were thoroughly characterized by their spectral analyses. These compounds have been screened for their in vitro antitubercular activity against Mycobacterium tuberculosis H37Ra and Mycobacterium bovis (BCG). The compounds 8a, 8c, and 8e exhibited notable in vitro antitubercular activity compare to the reference, Rifampicin. Molecular docking study has also been performed to know the binding mode of these analogs in to the active site of DprE1 enzyme. The synthesized compounds were also evaluated for their in vitro antibacterial activity and amongst them compound 8k has shown moderate activity against both gram-negative and gram-positive bacterial strains.